Aptamer-based Cell Recognition and Detection - Zheng, Liyan; Zhang, Qiang; Zhang, Yutong; Qiu, Liping; Tan, Weihong (Current Analytical Chemistry, 2022)
Cells, regarded as the structural and functional units of organisms, have become one of the most important objects in many research areas. Specific recognition and detection of malignant cells are critical for disease diagnosis, therapy and prognosis. Aptamers are short; single-stranded oligonucleotides screened from a random library by an in vitro technology termed “Systematic Evolution of Ligands by Exponential Enrichment” (SELEX) on the basis of their specific binding to target cargos. With the advantages of small size, easy synthesis, convenient modification, high chemical stability and low immunogenicity, aptamers have attracted broad attention in bioanalysis. Using intact living cells as the selection target, the cell-SELEX technology enables the generation of many aptamers that can specifically recognize molecular signatures of target cells. These aptamers have been extensively utilized in various cell-based research. In this mini-review, we focus on recent advances in aptamer-based recognition and detection of cells, particularly circulating tumor cells (CTCs).
Keywords: fluorescence detection